Cybersecurity and AI as enablers of economic resilience: A framework for sustainable growth in developing countries - Ali Siraj Ahmed; Rahmat Budiarto (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2025)
Digital transformation offers unprecedented opportunities for sustainable economic growth in developing countries. However, these benefits are accompanied by increased cybersecurity risks and challenges in integrating emerging technologies like artificial intelligence (AI). This paper proposes a conceptual framework that positions cybersecurity and AI as dual enablers of economic resilience aligned with Sustainable Development Goal 8 (SDG 8). The framework comprises three interconnected pillars: cybersecurity infrastructure, AI-driven economic transformation, and AI-enhanced cybersecurity mechanisms. A case study of Sudan illustrates how tailored interventions can foster secure, inclusive, and resilient digital economies in low- and middle-income contexts. The study highlights the importance of ethical governance, multi-stakeholder collaboration, and capacity building to maximize the benefits of AI while mitigating risks. Future research directions include empirical validation and policy experimentation to refine the framework and accelerate digital-led economic resilience in the Global South.